STUDI BERKAITAN DENGAN KOMITE AUDIT INDEPENDEN, PENGUNGKAPAN SUKARELA, DAN HARGA SAHAM - Desery Natalia Kinsy (Jurnal Ekonomis, 2018)
This study aims to examine the proportion of independent audit committees has an influence on voluntary disclosure in the annual report and test whether voluntary disclosure in the annual report of banking companies in the Indonesia Stock Exchange. This research uses the average data of stock price of company as dependent variable, intervening variable that is voluntary disclosure in annual report is measured using checklist item, independent variable in this research is proportion of independent audit committee which can be measured directly. The population in this study are all banking companies listed on the Indonesia Stock Exchange 2014-2016. Sample selection procedure using purposive sampling method and the number of samples obtained as many as 114 banking companies. The analysis used in this research includes descriptive statistical analysis, PLS data analysis, and Sobel test. From the hypothesis testing results, there was a significant negative effect between the proportion of the independent audit committee on voluntary disclosure in the annual report, the significant positive effect of voluntary disclosure in the annual report on stock prices, and the insignificant negative effect between the proportion of independent audit committees to stock prices. The study also found significant results that voluntary disclosure in the annual report deserves an intervening variable between the proportion of independent audit committees to stock prices.